2006
DOI: 10.2353/ajpath.2006.051329
|View full text |Cite
|
Sign up to set email alerts
|

Nephritogenic Lupus Antibodies Recognize Glomerular Basement Membrane-Associated Chromatin Fragments Released from Apoptotic Intraglomerular Cells

Abstract: Antibodies to dsDNA represent a classification criterion for systemic lupus erythematosus. Subpopulations of these antibodies are involved in lupus nephritis. No known marker separates nephritogenic from non-nephritogenic anti-dsDNA antibodies. It is not clear whether specificity for glomerular target antigens or intrinsic antibody-affinity for dsDNA or nucleosomes is a critical parameter. Furthermore, it is still controversial whether glomerular target antigen(s) is constituted by nucleosomes or by non-nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
218
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(231 citation statements)
references
References 49 publications
11
218
1
1
Order By: Relevance
“…We have previously identified chromatin fragments as the glomerular target structure for nephritogenic autoantibodies in lupus nephritis (12,13,38) (for review, see refs. 8 and 9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously identified chromatin fragments as the glomerular target structure for nephritogenic autoantibodies in lupus nephritis (12,13,38) (for review, see refs. 8 and 9).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that nephritogenic antibodies recognize chromatin fragments (10)(11)(12)(13) which bind glomerular basement membranes (GBMs) and matrix components with high affinity (14). These immune complexes were observed as electron-dense structures in GBMs and the mesangial matrix, and bound IgG was confined to electron-dense structures in both murine (12,14) and human (13) lupus nephritis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24] These antibodies were found to bind mainly nuclear antigens such as chromatin, histones and dsDNA, and/or components of the glomerular basement membrane. In particular, anti-dsDNA autoantibodies were found to be pathogenic and it has been shown that some anti-dsDNA autoantibodies can by themselves alter the gene expression profile of mesangial cell lines, turning on the expression of inflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental reports demonstrate the relationship between impaired clearance of apoptotic cells and SLE, and especially the involvement of C1q defects in SLE [64]. Kalaaji et al demonstrated that large chromatin fragments, derived from apoptotic cells, localize in the intraglomerular membrane in murine and human SLE [65], and that those intra-glomerular membrane-associated nucleosomes are targeted by anti-dsDNA autoantibodies in human lupus nephritis [66].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%